Mapping Rayleigh Wave Group Velocities from Ambient Noise in the Way Ratai Geothermal Field Using PiGraf Seismograph Prototypes (Rudarsko-geološko-naftni zbornik, 2025)
Since 2018, the research team has been investigating and developing a prototype sensor for recording seismic activity. An upgrade has been developed and must be evaluated, primarily to monitor ambient noise activities in the geothermal environment. This study aims to determine the group velocity of Rayleigh waves using ambient noise tomography (ANT) analysis in the Way Ratai geothermal region utilising four PiGraf seismograph prototypes. The acquisition method deploys a stationary inter-station around 5 kilometres (km) apart for seven consecutive days, with 100 samples per second (SPS). Fast marching surface tomography (FMST) has been utilised to generate group velocity from a cross-correlated time series, which produces tomographic images. The results showed that the ambient noise energy distribution originated from the northwest to the southeast, most likely from the sea. At the same time, the group velocity from the Green’s function group in the period range 0.2 s to 0.5 s, 0.5 s to 1 s, and 1 s to 5 s are 0.337 km/s, 0.415 km/s, and 0.427 km/s, respectively. These values are aligned within the dispersion curve’s velocity range of 0.3–0.8 km/s. The group velocity modelling of Rayleigh waves in the period range of 0.5 s to 1 s also identified a pattern corresponding with the geothermal potential area, confirming prior findings. However, the clarity of the cross-correlogram of the Green’s function group was identified as a topic for further investigation, suggesting adding more stations and longer measurement times.